Genetic and molecular factors in determining grain number per panicle of rice - Lu, Yue; Chuan, Mingli; Wang, Hanyao; Chen, Rujia; Tao, Tianyun; Zhou, Yong; Xu, Yang; Li, Pengcheng; Yao, Youli; Xu, Chenwu; Yang, Zefeng (Frontiers in Plant Science, 2022)
It was suggested that the most effective way to improve rice grain yield is to increase the grain number per panicle (GN) through the breeding practice in recent decades. GN is a representative quantitative trait affected by multiple genetic and environmental factors. Understanding the mechanisms controlling GN has become an important research field in rice biotechnology and breeding. In general, the regulation of rice GN is coordinately controlled by panicle architecture and branch differentiation, and many GN associated genes showed pleiotropic effect in regulating tillering, grain size, flowering time, and other domestication related traits. Recent investigations also revealed that GN determination is closely related to vascular development and the metabolism of some phytohormones. In this review, we summarize the recent findings in rice GN determination and discuss the genetic and molecular mechanisms of GN regulators.